Mother Tongue Interference Towards Students’ English Pronunciation: A Case Study of Fatoni University Students in English for Communication Course - Hayeesa-i, Tasneem (UNIB Press, 2023)
The main objective of this study is to investigate how different mother tongues (Pattani Malay, Thai, Arabic) affect students’ capability in pronouncing English words by selecting a case study from 30 samples of Fatoni university students in English for communication course. Besides, examining the percentage of students’ accuracy in pronouncing with their substituted phonemes in English initial, medial and final consonants. Also, discovering the other factors probably affect their English pronunciation. The research instruments used document analysis, a questionnaire, and pronunciation testing of 20 difficult English words which were selected from the previous studies of difficult or disappearing phonemes in all 3 mother-tongue groups compared to phonemes in English. The findings show that different mother tongues (Pattani Malay, Thai, and Arabic) have distinct effects on their pronunciation. There are different percentages of students who could accurately pronounce initial, medial, and final consonants in English in each group with various substituted phonemes that they automatically chose from the closest equivalences in their language. Furthermore, other factors such as bilingualism, studying abroad, and previously enrolling in an English phonetic course are likely to have a positive or negative impact on their English pronunciation, according to the research.